Signs in Urban Anti-sexualism Harassment Graffities: Semiotic Analysis - Maiyasa, Nabila; ., Mayasari; ., Arifuddin; Geubrina, Misla; ., Hidayati; Muchtar, Muhizar (KnE Social Sciences, 2023)
In this study, the researcher focuses mainly on the analysis of the visual and verbal signs and how the meaning of semiotic signs is realized in graffities. This study is based on library research and uses the descriptive-qualitative method to analyze the data. The data for this study is ten urban anti-sexualism harassment graffities, collected by downloading the images from the websites of Pinterest and Google. Graffiti is a form of visual communication that mostly consist of writings and drawings that have been made on public surfaces, mainly the walls. The theory for visual signs was used to analyze the data of the semiotic Triadic Model proposed by Charles Sanders Peirce, whereas the theory of Dyer was used to analyze verbal signs. The analysis revealed that visual signs mainly indicate character movement in graffiti and emotions. The verbal signs support visual signs by highlighting some aspects in graffiti to convey information about how people should be more concerned about anti-sexual harassment issues that occur in life. In addition, the analysis of this study also shows that meaningful events are created by the relationship between visual and verbal signs contained in each graffiti. Keywords: semiotics, graffiti, signs, Peirce, Dyer